Involvement of KV3.4 Channel in Parkinson's Disease: A Key Player in the Control of Midbrain and Striatum Differential Vulnerability during Disease Progression? - Giorgia Magliocca; Emilia Esposito; Michele Tufano; Ilaria Piccialli; Valentina Rubino; Valentina Tedeschi; Maria Jose Sisalli; Flavia Carriero; Giuseppina Ruggiero; Agnese Secondo; Lucio Annunziato; Antonella Scorziello; et al. (MDPI AG, 2024)
Parkinson's disease (PD), the second most common neurodegenerative disease in the elderly, is characterized by selective loss of dopaminergic neurons and accumulation of α-synuclein (α-syn), mitochondrial dysfunction, Ca2+ dyshomeostasis, and neuroinflammation. Since current treatments for PD merely address symptoms, there is an urgent need to identify the PD pathophysiological mechanisms to develop better therapies. Increasing evidence has identified KV3.4, a ROS-sensitive KV channel carrying fast-inactivating currents, as a potential therapeutic target against neurodegeneration. In fact, it has been hypothesized that KV3.4 channels could play a role in PD etiopathogenesis, controlling astrocytic activation and detrimental pathways in A53T mice, a well-known model of familial PD. Here, we showed that the A53T midbrain, primarily involved in the initial phase of PD pathogenesis, displayed an early upregulation of the KV3.4 channel at 4 months, followed by its reduction at 12 months, compared with age-matched WT. On the other hand, in the A53T striatum, the expression of KV3.4 remained high at 12 months, decreasing thereafter, in 16-month-old mice. The proteomic profile highlighted a different detrimental phenotype in A53T brain areas. In fact, the A53T striatum and midbrain differently expressed neuroprotective/detrimental pathways, with the variation of astrocytic p27kip1, XIAP, and Smac/DIABLO expression. Of note, a switch from protective to detrimental phenotype was characterized by the upregulation of Smac/DIABLO and downregulation of p27kip1 and XIAP. This occurred earlier in the A53T midbrain, at 12 months, compared with the striatum proteomic profile. In accordance, an upregulation of Smac/DIABLO and a downregulation of p27kip1 occurred in the A53T striatum only at 16 months, showing the slowest involvement of this brain area. Of interest, HIF-1α overexpression was associated with the detrimental profile in midbrain and its major vulnerability. At the cellular level, patch-clamp recordings revealed that primary A53T striatum astrocytes showed hyperpolarized resting membrane potentials and lower firing frequency associated with KV3.4 ROS-dependent hyperactivity, whereas primary A53T midbrain astrocytes displayed a depolarized resting membrane potential accompanied by a slight increase of KV3.4 currents. Accordingly, intracellular Ca2+ homeostasis was significantly altered in A53T midbrain astrocytes, in which the ER Ca2+ level was lower than in A53T striatum astrocytes and the respective littermate controls. Collectively, these results suggest that the early KV3.4 overexpression and ROS-dependent hyperactivation in astrocytes could take part in the different vulnerabilities of midbrain and striatum, highlighting astrocytic KV3.4 as a possible new therapeutic target in PD.